Pengaruh Latihan Zumba Terhadap Resting Heart Rate dan Peak Expiratory Flow Rate Pada Wanita Usia Dewasa Muda - Ruberto, Sandro; Supatmo, Yuswo; Setiawati, Erna; Ambarwati, Endang (RSUP Dr. Kariadi, 2021)
Introduction : Lack of physical activity is one of the risk factor for general mortality, therefore it is important to do regular physical activity. Zumba is one of the most popular physical activity methods and it has a lot of benefits especially for cardiorespiratory fitness. Objective : To determine the effect of Zumba exercise on Resting Heart Rate (RHR) and Peak Expiratory Flow Rate (PEFR) as an indicator of cardiorespiratory fitness. Methods : This is an experimental study using pre-test and post-test control group design. In this study, 26 females were divided in 2 groups (intervention and control group). Zumba exercise was given to intervention group 2 times a week (60 minutes per session) for 8-weeks exercise program. Zumba exercise was done virtually using videos provided by Zumba instructor. RHR measurement was carried out independently by research subjects in the morning when they woke up. PEFR measurement was done by using a peak-flow meter. Results : After 8-weeks Zumba exercise program, there was insignificant decreased of RHR from 71 ± 9 beat per minute to 70 ± 8 beats per minute (p>0,005). PEFR was significantly increased from 364 ± 36 liter/minute to 397 ± 42 liter/minute (p<0,005). But, there was no significant difference compared to control group. Conclusion : Zumba exercise can increase PEFR and decrease RHR, but it is not significantly different from the control group. It can be caused by the accuracy of the Zumba exercise is not supervised by the instructor. Keywords : peak expiratory flow rate, resting heart rate, zumba